STRATEGIES CONSTRAINS IN RENDERING ISLAMIC RELIGIOUS COLLOCATIONS FROM ARABIC INTO ENGLISH - Mubarak, Amin Ali Al (Universitas Kuningan, 2019)
This particular study investigates the problems found in the strategies adopted by students in translating certain lexical collocations of the Islamic religious texts. For that purpose, a purposive sample of 41 B.A, English students enrolled in the academic year of 2017-2018 at the Arts College had been selected as participants in this study. Thus, the primary objective of the study is to determine if these Sudanese students faced any problem when translating Islamic religious collocations from Arabic into English. Therefore, the researcher employed the descriptive approach to identify the problems faced by students in using several strategies for translation. As for data collection method, a test, which consisted of specific lexical collocations terms, had been carried out to analyse the obstacles that the students faced when translating Islamic religious collocations terms from Arabic into English. Hence, some main issues that were identified from the findings were reviewed in a wholesome manner and wherever possible, links were made to associate the themes to the literature examined, besides further extending the research scope via comparison with other literature in light of the finding. Finally, some recommendations are given at the end of the research mainly for students to improve their skills in translating Islamic lexical collocations from Arabic into English.